Structural and magnetic properties of La2Ni1−xZnxMnO6 compounds. (28th October 2021) - Pramanik, Debabrata; Mukherjee, S; Dan, Shovan; Poddar, Asok; Dasgupta, Papri; Jayavel, R
Abstract: Compounds of a randomly diluted ferromagnetic system La2 Ni1− x Zn x MnO6 (LNZ x MO) ( x = 0.2, 0.4, 0.6, 0.8) have been synthesized by Sol-gel technique. These compounds possess monoclinic structure ( P 21 / n, space group number 14) at room temperature. Below the Curie temperature ( T C ), LNZ x MO are soft ferromagnets with low values of remanent magnetization ( M r ) and coercivity ( H c ) for x less than equal to 0.6. The exchange interaction is of short range nature. Freezing of clusters is observed in LNZ0.8 MO below T = 10 K. Although, LNZ x MO is a randomly diluted ferromagnetic system, no signature of Griffiths phase (GP) is found.